Defense Mechanism of Lots-O'-Huggin' Bear in Toy Story 3 (2010): Sigmund Freud Psychoanalytic Approach : Mekanisme Pertahanan Diri pada Lots-O'-Huggin' Bear dalam Toy Story 3 (2010): Pendekatan Psikoanalisis Sigmund Freud - Muhammad Adi Kurniawan; Nurhidayat (University of Surakarta, 2025)
This research analyzes the dynamic of the character Lots-o'-huggin' Bear (Lotso) in film titled “Toy Story 3” (2010) through Freud’s psychoanalytic view. The purposes of this research are to reveal what kind of mechanism, the reason behind his such defensive behavior, and how he creates conflict in the film. This is qualitative research by collecting qualitative data. The primary data was taken from film Toy Story 3 (2010) in the form of dialogue, story depictions, ideas, and various phenomena narrated in the film. The technique of collecting data used is note taking and image capturing. The result found three types of defense mechanism used by Lotso, namely denial, displacement, and projection. The use of defense mechanism is from trauma caused him neurotic anxiety by a conflict between the id and ego. Furthermore, Lotso’s contribution to creating conflict in the film are manipulation, force, and betrayal. From the research results, literary enthusiasts are expected to open up insights that characters in films do not only function as actors in a story but also as representations of complex psychological conditions. Additionally, this study can be used as a reference for researchers in using a psychological approach to analyze characters in films.